Transport and deposition of inhaled fibers in a realistic female airway model: A combined experimental and numerical study - Prinz, František; Kánská, Jana; Elcner, Jakub; Hájek, Ondřej; Kummerländer, Adrian; Krause, Mathias J; Jícha, Miroslav; Lízal, František (Computers in biology and medicine, 2025)
This study presents a combined experimental and numerical investigation of fiber transport and deposition in a realistic model of the female respiratory tract, extending to the seventh generation of branching. Numerical simulations were performed using the Euler-Lagrange Euler-Rotation (ELER) method, an efficient alternative to conventional Finite Volume Methods that benefits from explicit formulation and vast scalability, enabling fast parallelization on high-performance clusters. The ELER method was coupled with the Lattice Boltzmann Method (LBM) to simulate fiber dynamics under a realistic inspiratory flow profile. Experimental validation was conducted using an identical physical airway replica. The results demonstrated good agreement between simulations and experiments in the upper airways and trachea, with some discrepancies in the bifurcations, likely owing to the challenges of modeling complex turbulent flow with ELER. This method is more accurate than corresponding effective diameter simulations. Deposition patterns were analyzed as a function of fiber dimensions, revealing higher accuracy of the ELER method for smaller particles and confirming the tendency of higher aspect ratio fibers to penetrate deeper into the lungs. The orientation-dependent deposition mechanism was deployed, underscoring the importance of solving the actual orientations of the fibers. While advancing our understanding of fiber transport in female airways, the findings also reveal limitations in current numerical techniques, particularly in bifurcations. This study emphasizes the distinct behavior of fibrous versus spherical particles, with fibers exhibiting a greater propensity to reach deeper lung regions, which has significant implications for inhalation toxicology and drug delivery.
Keywords: Respiratory System; In silico; Fiber transport; Humans; Euler–Lagrange Euler-rotation; Administration, Inhalation; Trachea; In vitro; Computer Simulation; Female; Models, Biological; Lattice Boltzmann method; Lung; lidé; plíce; dýchací soustava; Female airway geometry; ženské pohlaví; počítačová simulace; trachea; biologické modely; aplikace inhalační; Deposition